THE HISTORY OF STUDYING THE VOCABULARY OF NATIONAL CUSTOMS IN THE UZBEK LANGUAGE (Journal of Universal Science Research, 2025)
This article explores the history of studying the vocabulary of national customs in the Uzbek language. It traces the development of linguistic research from early historical periods, such as the influence of Arabic and Persian, through the Russian and Soviet eras, to modern scholarly efforts. The article highlights key methodologies used in the study of Uzbek vocabulary, including etymology, dialectology, semantics, and discourse analysis. It emphasizes the importance of understanding the cultural and historical context behind the vocabulary of national customs, contributing to a deeper appreciation of Uzbek linguistic heritage.